Perancangan Sistem Udara Bertekanan Untuk Cabin Pressurization dan Praktikum Mahasiswa - Febrian Setiaji; Teguh Wibowo (Politeknik Negeri Bengkalis, 2021)
The compressed air system is also called a vital system because it functions as a provider of compressed air for activities such as lifting and holding, turning and pressing, and even can be used for cleaning. In addition to those activities, it can also be used as a supply to the cabin pressurization simulation tool so that the pressure in the cabin can match the pressure of the aircraft when it is on the ground.This final project entitled